Ecological ceramsite, preparation method thereof and wastewater treatment method
The preparation of ceramsite from copper tailings addresses the complexity and cost issues of existing wastewater treatment by effectively removing lead ions and phosphorus, stabilizing heavy metals, and promoting resource utilization.
Patent Information
- Application Number
- CN202411422206.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
Existing wastewater treatment methods for lead ions and phosphorus are complex and costly, posing environmental and health risks due to untreated discharge, and there is a need for a simpler and more economical solution.
A method involving the preparation of ecological ceramsite by sintering copper tailings with bauxite and calcium carbonate, forming a porous structure that can adsorb and stabilize lead ions and phosphorus, utilizing copper tailings as a resource.
The ceramsite effectively removes over 90% of lead ions and phosphorus from wastewater with a simple process, reducing production costs and environmental impact, while also stabilizing heavy metals and promoting resource utilization.
Smart Images

Figure CN119241209A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wastewater treatment, and in particular to an ecological ceramsite and a preparation method thereof and a wastewater treatment method. Background Art
[0002] Wastewater containing lead ions or phosphorus comes from a wide range of sources, mainly industrial wastewater, agricultural wastewater, mining water, urban domestic wastewater, etc.
[0003] Untreated wastewater containing lead ions or phosphorus discharged into water bodies will seriously pollute rivers, lakes and oceans, destroy aquatic ecosystems, and especially endanger the ecological environment of high-altitude and ecologically fragile areas, affecting water quality and the health of aquatic organisms. If untreated wastewater containing lead ions or phosphorus infiltrates into the ground, lead ions or phosphorus may contaminate groundwater and soil, causing soil quality to deteriorate, affecting crop growth and food safety. Lead ions are seriously harmful to human health and can accumulate through the food chain. Long-term intake can cause damage to organs such as nerves, kidneys, and liver. Although phosphorus is a nutrient element, excessive intake or eutrophication of water bodies can cause algal blooms, produce toxins, and affect human health.
[0004] The treatment of wastewater containing lead ions or phosphorus has multiple important implications, not only for environmental protection, but also for public health and sustainable development.
[0005] However, for wastewater containing lead ions or phosphorus, the existing wastewater treatment methods have the defects of complex treatment agent preparation process and high production cost, which increases the production cost of the wastewater treatment method. Therefore, it is necessary to improve it. Summary of the invention
[0006] The purpose of this application is to provide an ecological ceramsite and a preparation method thereof and a wastewater treatment method to solve the above problems.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] A method for preparing ecological ceramsite comprises: sintering a mixture of copper tailings, a binder and a pore-forming agent to obtain ecological ceramsite.
[0009] According to an embodiment of the present application, the binder includes bauxite, and the pore former includes calcium carbonate.
[0010] According to an embodiment of the present application, the mass ratio of the copper tailings to the binder and the pore-forming agent is 3.5:(1-3):(0.8-3.5).
[0011] According to an embodiment of the present application, the particle size of the copper tailings is ≤1 mm, the particle size of the binder is ≤1 mm, and the particle size of the pore-forming agent is ≤1 mm.
[0012] According to an embodiment of the present application, the temperature of the sintering process is 1050-1100°C.
[0013] According to an embodiment of the present application, the sintering treatment time is 10 to 30 minutes.
[0014] The present application also provides an ecological ceramsite, which is prepared by the preparation method of the ecological ceramsite described above.
[0015] The present application also provides a wastewater treatment method, comprising: mixing wastewater with the ecological ceramsite described above, reacting, and after the reaction is completed, filtering out the ecological ceramsite to obtain treated wastewater; wherein the wastewater includes lead ions or phosphorus.
[0016] According to an embodiment of the present application, the mass volume ratio of the ecological ceramsite to the wastewater is 10 to 20 g / L.
[0017] According to the embodiments of the present application, the pH of the wastewater is 1.5 to 2; the reaction time is 24 to 36 hours; and the removal rate of lead ions or phosphorus in the wastewater is more than 90%.
[0018] Compared with the prior art, the beneficial effects of this application include:
[0019] The preparation method of the ecological ceramsite of the present application can solidify / stabilize the heavy metal elements in the copper tailings, reduce the dissolution rate of the heavy metal elements, and realize the resource utilization of the copper tailings. In addition, the ecological ceramsite of the present application can be used as a wastewater treatment agent to remove lead ions or phosphorus in the wastewater. Since the preparation method of the ecological ceramsite has the advantages of simple operation and low production cost, the present application improves the defects of the treatment agent preparation process being complex and the production cost being high in the existing wastewater treatment process.
[0020] The ecological ceramsite of the present application has a porous structure and can be used to remove lead ions or phosphorus in wastewater with good removal effect.
[0021] The wastewater treatment method of the present application has the advantages of simple operation, low production cost and excellent wastewater treatment effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0023] Figure 1 This is a flow chart of the method for preparing ecological ceramsite in this application;
[0024] Figure 2This is a flow chart of the wastewater treatment method in this application. DETAILED DESCRIPTION
[0025] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0026] The present application provides a method for preparing ecological ceramsite, comprising: sintering a mixture of copper tailings, a binder and a pore-forming agent to obtain ecological ceramsite.
[0027] Copper tailings have low content of valuable components and contain trace amounts of heavy metal elements, and it is difficult to realize resource utilization of them by traditional methods. The present application can wrap the heavy metal elements in copper tailings inside ceramsite to achieve the purpose of solidification / stabilization, significantly reduce the dissolution rate of heavy metal elements, reduce the risk of pollution to water bodies and soil, and realize the resource utilization of copper tailings. Moreover, the ecological ceramsite of the present application can be used as a treatment agent to remove lead ions or phosphorus in wastewater. The preparation method of ecological ceramsite has the advantages of simple operation and low production cost, which improves the defects of complex treatment agent preparation process and high production cost in the existing wastewater treatment process.
[0028] Furthermore, the copper tailings may be copper tailings from high-altitude and ecologically fragile areas.
[0029] According to an embodiment of the present application, the binder includes bauxite, and the pore-forming agent includes calcium carbonate. Bauxite is used to regulate the mineral components of ceramsite, and calcium carbonate has a good foaming effect in the process of preparing ceramsite. Specifically, in the preparation process of ecological ceramsite, bauxite can be used as a binder to combine other raw materials together, and the chemical composition of bauxite can also be used to affect the final mineral phase composition of ecological ceramsite, which is beneficial to improve the comprehensive performance of ecological ceramsite. Calcium carbonate decomposes at high temperatures to produce carbon dioxide gas, which expands and escapes inside the material, forming a large number of tiny pores in the ceramsite. Since the decomposition temperature of calcium carbonate is moderate and the decomposition products are easy to discharge, its foaming effect is usually good, and an ecological ceramsite product with high porosity, uniform pore size distribution and excellent performance can be prepared.
[0030] According to an embodiment of the present application, the mass ratio of the copper tailings to the binder and the pore-forming agent is 3.5:(1-3):(0.8-3.5). When the mass of the copper tailings, the binder and the pore-forming agent is within the above range, the mineral composition, strength and performance of the ceramsite meet the requirements. If the amount of binder is too high, the copper tailings will be less absorbed, which is not conducive to the overall performance of the ecological ceramsite. If the amount of binder is too low, the copper tailings and other raw materials cannot be effectively and firmly combined together, resulting in a lower strength of the ecological ceramsite. If the amount of pore-forming agent is too high, too many pores will be generated inside the ecological ceramsite, and the excessive porosity will reduce the density and strength of the ecological ceramsite, resulting in a decrease in the adsorption performance of the ecological ceramsite; if the amount of pore-forming agent is too low, it will not be possible to form enough pores inside the ecological ceramsite, resulting in a lower pore ratio inside the ceramsite, affecting the adsorption performance of the ecological ceramsite.
[0031] Exemplarily, the mass ratio of the copper tailings to the binder and the pore-forming agent is 3.5:1:0.8, 3.5:1:3.5, 3.5:1.5:1.5, 3.5:3:0.8, 3.5:3:3.5 or any value between 3.5:(1-3):(0.8-3.5).
[0032] According to an embodiment of the present application, the particle size of the copper tailings is ≤1 mm, the particle size of the binder is ≤1 mm, and the particle size of the pore-forming agent is ≤1 mm. Thus, each reaction raw material has a smaller particle size, which helps to form a more uniform ceramsite structure during the sintering process, thereby improving the overall uniformity and consistency of the ceramsite. Moreover, raw materials with smaller particle sizes have a larger surface area, which can increase the contact area between the raw materials, thereby improving the reaction efficiency and speed during the sintering process, and helping to form an ideal ceramsite structure.
[0033] According to the embodiment of the present application, the temperature of the sintering treatment is 1050-1100°C. Within the above sintering treatment temperature range, it is beneficial to obtain ecological ceramsite with excellent comprehensive performance. If the sintering treatment temperature is too low, the strength of the ecological ceramsite will be insufficient; if the sintering treatment temperature is too high, it will affect the structure of the final product and thus affect its performance, and also increase energy consumption.
[0034] Illustratively, the temperature of the sintering process may be 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C or any value between 1050 and 1100°C.
[0035] According to an embodiment of the present application, the sintering treatment time is 10 to 30 minutes. In this way, it can be ensured that sufficient reaction occurs between the raw materials to form a porous product structure with stable structure. If the sintering treatment time is too short, it may lead to insufficient reaction between the raw materials, affecting the structural stability and physical properties of the ceramsite. If the sintering treatment time is too long, the excessive sintering time will increase energy consumption and increase production costs; and high temperature for too long may cause certain components in the ceramsite to change, causing the performance of the ceramsite to deviate from expectations.
[0036] For example, the sintering time may be 10 min, 15 min, 20 min, 25 min, 30 min or any value between 10 and 30 min.
[0037] The present application also provides an ecological ceramsite, which is prepared by the preparation method of the ecological ceramsite described above.
[0038] The present application also provides a wastewater treatment method, comprising: mixing wastewater with the ecological ceramsite described above, reacting, and after the reaction is completed, filtering out the ecological ceramsite to obtain treated wastewater; wherein the wastewater includes lead ions or phosphorus.
[0039] The ecological ceramsite of the present application can effectively remove lead ions or phosphorus in wastewater. Specifically, the ceramsite has a porous structure and has the performance of physical adsorption, and the mineral components of the ceramsite can also chemically adsorb lead ions or phosphorus in wastewater, thereby achieving the purpose of removing lead ions or phosphorus in wastewater.
[0040] According to an embodiment of the present application, the mass volume ratio of the ecological ceramsite to the wastewater is 10 to 20 g / L.
[0041] Exemplarily, the mass volume ratio of the ecological expanded clay to the wastewater can be 10g / L, 11g / L, 12g / L, 13g / L, 14g / L, 15g / L, 16g / L, 17g / L, 18g / L, 19g / L, 20g / L or any value between 10 and 20g / L.
[0042] According to an embodiment of the present application, the pH of the wastewater is 1.5-2; for example, the pH of the wastewater may be 1.5, 2 or any value between 1.5 and 2.
[0043] The reaction time is 24 to 36 hours; thus, it can be ensured that the ceramsite has enough time to contact with the lead ions or phosphorus in the wastewater, and the lead ions or phosphorus in the wastewater are effectively fixed. If the reaction time is too short, the lead ions or phosphorus may not be in sufficient contact with the ceramsite, and the lead ions or phosphorus may not be effectively converted into a stable form. If the reaction time is too long, it will increase energy consumption, increase treatment costs, and reduce the treatment capacity of the treatment system, affecting the overall efficiency of wastewater treatment.
[0044] Illustratively, the reaction time is 24 h, 28 h, 32 h, 36 h or any value between 24 and 36 h.
[0045] Furthermore, the reaction is carried out under stirring conditions, and the stirring includes shaking stirring.
[0046] And / or, the removal rate of lead ions or phosphorus in the wastewater is above 90%.
[0047] It is difficult to maintain soil fertility for a long time in high-altitude and ecologically fragile areas, so plant ecological restoration in high-altitude and ecologically fragile areas is more complex and difficult.
[0048] The ecological ceramsite of the present application can also be used for plant ecological restoration. The ecological ceramsite product of the present application has the characteristics of porosity, so the ecological ceramsite product of the present application has the function of retaining water and fertilizer, which has positive significance for plant ecological restoration in high-cold and ecologically fragile areas.
[0049] As used herein:
[0050] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0051] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0052] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0053] In these examples, parts and percentages are by mass unless otherwise indicated.
[0054] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0055] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0056] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0057] Example 1
[0058] A method for preparing ecological ceramsite, reference Figure 1 , including the following steps:
[0059] Copper tailings, bauxite and calcium carbonate were mixed in a mass ratio of 3.5:1.5:1.5, calcined at 1050°C for 20 min, and cooled to obtain ecological ceramsite.
[0060] refer to Figure 2, the ecological ceramsite prepared in Example 1 was added to the wastewater containing lead ions at a pH of 1.5, so that the mass volume ratio of the ecological ceramsite to the wastewater was 15 g / L, and the conical flask of the lead ion wastewater was shaken and stirred on a shaker for 24 hours for reaction. After the reaction was completed, the ecological ceramsite was filtered to remove the lead ion content in the treated wastewater, and the lead ion removal rate was calculated according to the lead ion content in the wastewater before and after treatment. The lead ion removal rate was 99.67%.
[0061] The ecological ceramsite prepared in Example 1 was added to phosphorus-containing wastewater with a pH of 2, so that the mass volume ratio of the ecological ceramsite to the phosphorus-containing wastewater was 20 g / L, and the wastewater conical flask was shaken and stirred on a shaker for 24 hours to react. After the reaction was completed, the ecological ceramsite was filtered to remove the phosphorus content in the treated wastewater, and the phosphorus removal rate was calculated based on the phosphorus content in the wastewater before and after treatment. The phosphorus removal rate was 97.85%.
[0062] Example 2
[0063] A method for preparing ecological ceramsite comprises the following steps:
[0064] Copper tailings, bauxite and calcium carbonate were mixed in a mass ratio of 3.5:1:0.8, calcined at 1050°C for 20 min, and cooled to obtain ecological ceramsite.
[0065] The ecological ceramsite prepared in Example 2 was added to the wastewater containing lead ions at a pH of 1.5, so that the mass volume ratio of the ecological ceramsite to the wastewater was 15 g / L, and the conical flask of the lead ion wastewater was shaken and stirred on a shaker for 24 hours for reaction. After the reaction was completed, the ecological ceramsite was filtered to remove the lead ion content in the treated wastewater, and the lead ion removal rate was calculated according to the content of lead ions in the wastewater before and after treatment. The lead ion removal rate was 92.27%.
[0066] The ecological ceramsite prepared in Example 2 was added to phosphorus-containing wastewater with a pH of 2, so that the mass volume ratio of the ecological ceramsite to the wastewater was 20 g / L, and the wastewater conical flask was shaken and stirred on a shaker for 24 hours to react. After the reaction was completed, the ecological ceramsite was filtered to remove the phosphorus content in the treated wastewater, and the phosphorus removal rate was calculated based on the phosphorus content in the wastewater before and after treatment. The phosphorus removal rate was 91.32%.
[0067] Example 3
[0068] A method for preparing ecological ceramsite comprises the following steps:
[0069] Copper tailings, bauxite and calcium carbonate were mixed in a mass ratio of 3.5:3:3.5, calcined at 1050°C for 20 min, and then cooled to obtain ecological ceramsite.
[0070] The ecological ceramsite prepared in Example 3 was added to the wastewater containing lead ions at a pH of 1.5, so that the mass volume ratio of the ecological ceramsite to the wastewater was 20 g / L, and the conical flask of the lead ion wastewater was shaken and stirred on a shaker for 24 hours for reaction. After the reaction was completed, the ecological ceramsite was filtered to remove the lead ion content in the treated wastewater, and the lead ion removal rate was calculated based on the content of lead ions in the wastewater before and after treatment. The lead ion removal rate was 99.23%.
[0071] The ecological ceramsite prepared in Example 3 was added to phosphorus-containing wastewater with a pH of 2, so that the mass volume ratio of the ecological ceramsite to the wastewater was 20 g / L, and the wastewater conical flask was shaken and stirred on a shaker for 24 hours to react. After the reaction was completed, the ecological ceramsite was filtered to remove the phosphorus content in the treated wastewater, and the phosphorus removal rate was calculated based on the phosphorus content in the wastewater before and after treatment. The phosphorus removal rate was 95.62%.
[0072] Example 4
[0073] A method for preparing ecological ceramsite comprises the following steps:
[0074] Copper tailings, bauxite and calcium carbonate were mixed in a mass ratio of 3.5:1.5:1.5, calcined at 1100°C for 10 min, and then cooled to obtain ecological ceramsite.
[0075] The ecological ceramsite prepared in Example 4 was added to the wastewater containing lead ions at a pH of 1.5, so that the mass volume ratio of the ecological ceramsite to the wastewater was 15 g / L, and the conical flask of the lead ion wastewater was shaken and stirred on a shaker for 24 hours for reaction. After the reaction was completed, the ecological ceramsite was filtered to remove the lead ion content in the treated wastewater, and the lead ion removal rate was calculated according to the content of lead ions in the wastewater before and after treatment. The lead ion removal rate was 93.36%.
[0076] The ecological ceramsite prepared in Example 4 was added to phosphorus-containing wastewater with a pH of 2, so that the mass volume ratio of the ecological ceramsite to the wastewater was 15 g / L, and the wastewater conical flask was shaken and stirred on a shaker for 24 hours to react. After the reaction was completed, the ecological ceramsite was filtered to remove the phosphorus content in the treated wastewater, and the phosphorus removal rate was calculated based on the phosphorus content in the wastewater before and after treatment. The phosphorus removal rate was 92.78%.
[0077] Example 5
[0078] A method for preparing ecological ceramsite comprises the following steps:
[0079] Copper tailings, bauxite and calcium carbonate were mixed in a mass ratio of 3.5:1.5:1.5, calcined at 1050°C for 30 min, and then cooled to obtain ecological ceramsite.
[0080] The ecological ceramsite prepared in Example 5 was added to the wastewater containing lead ions at a pH of 1.5, so that the mass volume ratio of the ecological ceramsite to the wastewater was 10 g / L, and the conical flask of the lead ion wastewater was shaken and stirred on a shaking table for 24 hours for reaction. After the reaction was completed, the ecological ceramsite was filtered to remove the lead ion content in the treated wastewater, and the lead ion removal rate was calculated according to the content of lead ions in the wastewater before and after treatment. The lead ion removal rate was 97.56%.
[0081] The ecological ceramsite prepared in Example 5 was added to phosphorus-containing wastewater with a pH of 2, so that the mass volume ratio of the ecological ceramsite to the wastewater was 20 g / L, and the wastewater conical flask was shaken and stirred on a shaker for 24 hours to react. After the reaction was completed, the ecological ceramsite was filtered to remove the phosphorus content in the treated wastewater, and the phosphorus removal rate was calculated based on the phosphorus content in the wastewater before and after treatment. The phosphorus removal rate was 98.38%.
[0082] Example 6
[0083] Copper tailings, bentonite and calcium carbonate were mixed in a mass ratio of 3.5:1.5:1.5, calcined at 1050°C for 20 min, and cooled to obtain ecological ceramsite.
[0084] The prepared ecological ceramsite was added to the wastewater containing lead ions at a pH of 1.5, so that the mass volume ratio of ecological ceramsite to wastewater was 15g / L. The conical flask of lead ion wastewater was shaken and stirred on a shaker for 24 hours to react. After the reaction, the ecological ceramsite was filtered to remove the lead ion content in the treated wastewater, and the lead ion removal rate was calculated based on the lead ion content in the wastewater before and after treatment. The lead ion removal rate was 21.6%.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0086] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing ecological ceramsite, characterized in that: include: The mixture of copper tailings, binder and pore-forming agent is sintered to obtain ecological ceramsite.
2. The method for preparing ecological ceramsite according to claim 1, characterized in that: The binder includes bauxite, and the pore former includes calcium carbonate.
3. The method for preparing ecological ceramsite according to claim 2, characterized in that: The mass ratio of the copper tailings to the binder and the pore-forming agent is 3.5:(1-3):(0.8-3.5).
4. The method for preparing ecological ceramsite according to claim 1, characterized in that: The particle size of the copper tailings is ≤1 mm, the particle size of the binder is ≤1 mm, and the particle size of the pore-forming agent is ≤1 mm.
5. The method for preparing ecological ceramsite according to claim 1, characterized in that: The sintering temperature is 1050-1100°C.
6. The method for preparing the ecological ceramsite according to any one of claims 1 to 5, characterized in that: The sintering time is 10 to 30 minutes.
7. An ecological ceramsite, characterized in that: The ecological ceramsite is prepared by the preparation method of the ecological ceramsite according to any one of claims 1 to 6.
8. A method for treating wastewater, characterized in that: include: The wastewater is mixed with the ecological ceramsite described in claim 7 to react, and after the reaction is completed, the ecological ceramsite is filtered out to obtain treated wastewater; wherein the wastewater includes lead ions or phosphorus.
9. The wastewater treatment method according to claim 8, characterized in that: The mass volume ratio of the ecological ceramsite to the wastewater is 10 to 20 g / L.
10. The wastewater treatment method according to claim 8 or 9, characterized in that: The pH of the wastewater is 1.5 to 2; the reaction time is 24 to 36 hours; and the removal rate of lead ions or phosphorus in the wastewater is more than 90%.
Citation Information
Patent Citations
Copper mine tailing slag porous ceramic material and preparation method thereof
CN102924113A
